2016
DOI: 10.1136/bmjopen-2016-011773
|View full text |Cite
|
Sign up to set email alerts
|

Improving the well-being of men by Evaluating and Addressing the Gastrointestinal Late Effects (EAGLE) of radical treatment for prostate cancer: study protocol for a mixed-method implementation project

Abstract: IntroductionRadiotherapy treatment for prostate cancer can cause bowel problems, which may lead to severe difficulties for cancer survivors including limiting travel, work or socialising. These symptoms can appear at any time following radiotherapy. This study focuses on the early identification and protocol-based management of effects known to cause long-term, or even permanent, changes to the well-being of prostate cancer survivors. The rationale of this study is to improve the care offered to men and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…We started the observation three years after the radiotherapy and possibly the patho-physiological processes leading to urgency-related symptoms at that time had reached a steady level or diminished. Taking drugs like sterculia gum, increasing stool consistency and skipping meals are, according to clinical experience, ways to decrease the intensity of the urgency syndrome [22]. Possibly a major reason for the decreased intensity is that the survivors learn to cope with their urgency-related symptoms by varying means.…”
Section: Discussionmentioning
confidence: 99%
“…We started the observation three years after the radiotherapy and possibly the patho-physiological processes leading to urgency-related symptoms at that time had reached a steady level or diminished. Taking drugs like sterculia gum, increasing stool consistency and skipping meals are, according to clinical experience, ways to decrease the intensity of the urgency syndrome [22]. Possibly a major reason for the decreased intensity is that the survivors learn to cope with their urgency-related symptoms by varying means.…”
Section: Discussionmentioning
confidence: 99%
“…All statistical calculations were carried out using SPSS V23. (More details relating to ''materials and methods" for this study have previously been published [13]).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the significant impact that these bowel habit changes can have on quality of life, only one in five patients who develop gastrointestinal (GI) symptoms after pelvic radiotherapy are referred to a gastroenterologist [12]. A discussion of the possible reasons for this is given in a protocol paper for the EAGLE study [13], which aims to implement an innovative service to improve the care offered to men diagnosed with prostate cancer. The Optimising Radiotherapy Bowel Injury Therapy (ORBIT) trial [14] demonstrated that these symptoms can be diagnosed accurately and that they can be treated effectively at very modest cost compared to the cost of the cancer treatment itself, and that this approach leads to improvements in pelvic radiation-induced GI symptoms as measured by Inflammatory Bowel Disease Questionnaire-Bowel (IBDQ-B) scores.…”
Section: Introductionmentioning
confidence: 99%
“…We continue to use a learning in practice approach through surveys of staff and by speaking to sites directly. The higher levels within Velindre could be predicted due to their specialist interest in pelvic radiation disease for more than 5 years [15] evident in Brighton and Imperial, who have smaller teams of on-treat radiographers/nurses. This system is designed to help those patients significantly affected by pelvic radiation disease after 6 months and point them to the right help more effectively and quickly.…”
Section: The Experience So Farmentioning
confidence: 99%